Pengaruh Media Big Book Terhadap Kemampuan Membaca Permulaan di Kelas 1 Sekolah Dasar - Aina, Tasha; Devianty, Rina (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The beginning reading ability of grade 1 students at SD Negeri 105384 Pisang Pala is still low. This study aims to determine the effect of using Big Book media on improving students’ beginning reading skills. The study used a quantitative approach with a one-group pretest-posttest design involving 25 students as samples. Data analysis techniques included the Shapiro-Wilk normality test, homogeneity test, and paired sample t-test. The results showed that the data were normally distributed (Sig. pretest = 0.074 > 0.05; Sig. posttest = 0.014 > 0.05), homogeneous (Sig. = 0.042 < 0.05), and there was a significant difference between pretest and posttest scores (Sig. (2-tailed) = 0.000 < 0.05) with an average pretest score of 49.60 and posttest score of 82.00. These findings indicate that Big Book media effectively improves students’ beginning reading skills because it can attract interest in learning and facilitate understanding through attractive image visualization. Therefore, it is recommended as an alternative learning media in lower grades. This research implores the importance of using engaging and visual-based learning media to develop students’ beginning reading skills, especially in lower grades, which require a more interactive approach. Furthermore, the results of this study can serve as a basis for teachers to be more creative in selecting learning media that can enhance student interest and motivation. This research also opens opportunities for developing other visual-based learning media that can be tailored to the needs of students in primary education.